(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Objective: To report a case of liposomal doxorubicin induced anaphylaxis. Case Summary: A 43 year old female patient with metastatic carcinoma of endometrium was admitted to the hospital with chief complaints of abdominal pain, distention and vomiting. Due to the disease progression she was planned for chemotherapy with liposomal doxorubicin. But she developed anaphylactic reaction in the 1st dose and drug was stopped. Therapy was discontinued and she got recovered. Discussion: Liposomal doxorubicin is a formulation of doxorubicin packed in a liposome with a polyethylene glycol covering. The anaphylaxis occurred may be due to the surface component of the liposome itself and not due to the actual drug. The mechanism of reaction is probably due to complement activation. Conclusion: Anaphylaxis is a serious, sometimes life threatening condition which may require immediate intensive care support. Pre-treatment with diphenhydramine, dexamethasone and famotidine is found to be useful following liposomal doxorubicin infusion. Sometimes chemotherapy needs to be discontinued to avoid risk for patients.